An examination of the broaden-and-build model of positive emotions in military marriages: an actor-partner analysis - Baptist, Joyce A.; Goff, Briana S. Nelson (My University, 2012)
How emotional and cognitive processes combined to produce resilience in military marriages post-combat deployments was examined using the “broaden-and-build model of positive emotions” with 40 military couples. The model suggests that positive emotions expand, and negative emotions impede cognitive processes. Utilizing the Actor-Partner Interdependence Model, the association between positive and negative emotions on insight-causation was examined. Actor and partner effects were found for service members’ positive emotions and spouses’ negative emotions but not service members’ negative emotions and spouses’ positive emotions. Service members’ actor and partner effects were significantly stronger than spouses.’ Clinical and research implications are discussed.
Keywords: Military deployments; Dyadic analysis; Broaden-and-build; Positive emotions